Prime Archives in Material Science 2020
DOI: 10.37247/pams2ed.2.2020.20
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Different Electrolytes on Electrochemical Chloride Extraction to Recover Concrete Structures under Chloride Induced Corrosion

Abstract: Prime Archives in Material Science: 2 nd Edition 2 www.videleaf.com permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…EDT forms precipitates in microstructures of concrete (voids in cement pastes, steel-concrete interface and aggregate-cement paste interface), which results in corrosion-resistant concrete [ 14 , 15 , 16 , 17 , 18 , 19 ]. Like the conventional cathode protection method, EDT is effective for reducing chloride ion concentration in concrete exposed to high chloride environment [ 17 , 18 , 20 ]. For the propagation period, it was demonstrated that EDT re-passivates corroded rebars by re-alkalizing concrete in the vicinity of corroded steel, which suppresses corrosion rate.…”
Section: Introductionmentioning
confidence: 99%
“…EDT forms precipitates in microstructures of concrete (voids in cement pastes, steel-concrete interface and aggregate-cement paste interface), which results in corrosion-resistant concrete [ 14 , 15 , 16 , 17 , 18 , 19 ]. Like the conventional cathode protection method, EDT is effective for reducing chloride ion concentration in concrete exposed to high chloride environment [ 17 , 18 , 20 ]. For the propagation period, it was demonstrated that EDT re-passivates corroded rebars by re-alkalizing concrete in the vicinity of corroded steel, which suppresses corrosion rate.…”
Section: Introductionmentioning
confidence: 99%